2015
DOI: 10.1172/jci77250
|View full text |Cite
|
Sign up to set email alerts
|

Placenta growth factor augments airway hyperresponsiveness via leukotrienes and IL-13

Abstract: Airway hyperresponsiveness (AHR) affects 55%-77% of children with sickle cell disease (SCD) and occurs even in the absence of asthma. While asthma increases SCD morbidity and mortality, the mechanisms underlying the high AHR prevalence in a hemoglobinopathy remain unknown. We hypothesized that placenta growth factor (PlGF), an erythroblast-secreted factor that is elevated in SCD, mediates AHR. In allergen-exposed mice, loss of Plgf dampened AHR, reduced inflammation and eosinophilia, and decreased expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 78 publications
(132 reference statements)
3
33
0
Order By: Relevance
“…BALF cytokines in SCD mice with OVA-induced AAD have higher IL-5 [11], which is responsible for eosinophil chemotaxis and function. The lack of difference of IL-5 secretion in our study is supported by data from the study of Eiymo Mwa Mpollo et al [32], which also showed a lack of difference in IL-5 levelsbetween (chimeric) SCD and WT mice when exposed to HDM. Indeed, it has been shown that elevated IgE titers induce increased IL-5 production by helper T cells [33], and increased IL-5 levels can drive airway eosinophilia [34], possibly giving insight into a key difference between the models that may explain why OVA models induce more robust allergic inflammation in SCD mice, but HDM does not.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…BALF cytokines in SCD mice with OVA-induced AAD have higher IL-5 [11], which is responsible for eosinophil chemotaxis and function. The lack of difference of IL-5 secretion in our study is supported by data from the study of Eiymo Mwa Mpollo et al [32], which also showed a lack of difference in IL-5 levelsbetween (chimeric) SCD and WT mice when exposed to HDM. Indeed, it has been shown that elevated IgE titers induce increased IL-5 production by helper T cells [33], and increased IL-5 levels can drive airway eosinophilia [34], possibly giving insight into a key difference between the models that may explain why OVA models induce more robust allergic inflammation in SCD mice, but HDM does not.…”
Section: Discussionsupporting
confidence: 88%
“…While this may at first seem to contrast with our findings, if taken together, it fits into the clinical hypothesis that children with SCD have impaired lung function but not more severe asthma phenotypes [24, 25]. Indeed, Eiymo Mwa Mpollo et al [32] observed that chimeric SCD mice have elevated airway resistance at baseline when compared to WT mice, thus supporting this hypothesis. This group was able to link increased levels of placenta growth factor in SCD mice with increased airway resistance.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Unfortunately, erythropoiesis is metabolically demanding, and increases procoagulant autophagic vesicles (4). In addition, developing erythroblasts produce a number of vasoactive signaling molecules, including placental growth factor, that are associated with airway hyperactivity, monocyte activation, and pulmonary hypertension (5).…”
mentioning
confidence: 99%
“…2). Placenta growth factor, a VEGF family member overexpressed in SCD and now known to be stimulated by erythropoietin, heme iron and inflammatory cytokines, promotes to airway hyperreactivity in sickle cell mice via leukotrienes and IL-13 [44]. Thus, placenta growth factor appears to inflammatory pathways in the reactive airway disease frequently encountered in children with SCD.…”
Section: Inflammation: Role Of Dysregulated Innate Immunity In Scdmentioning
confidence: 99%